ESG Performance and Firm Value – Do Busy Directors Help? - Sabatini, Sondang Zenita; A. Utama, Cynthia (Universitas Prasetiya Mulya, 2023)
ESG is an important issue companies encounter when conducting business. The implementation of ESG with good performance will lead the company to be more prosperous and attractive to investors. This study examines how busy directors affect the increase in the value of companies that have good ESG performance within a sample of 41 public companies in Indonesia during the years 2017-2021. Data were obtained from Thomson Reuters and the companies’ annual reports. By using ESG score as a proxy for ESG performance variables and the percentage of busy directors’ presence in public companies, we can determine their influence on firm value. Panel data regression in e-views shows a positive and significant influence between ESG performance and firm value, and there is no significant effect between busy directors and firm value. Furthermore, we also find that the influence of busy directors as a moderator weakened the positive impact of ESG performance on firm value.